Paula Bunyan - Root, Phyllis; O'Malley, Kevin, 1961- (New York : Farrar, Straus and Giroux, 2009)
Recounts the exploits of Paul Bunyan's "little" sister, Paula, who lived in the North Woods, sang three-part harmony with the wolves, and used an angry bear for a foot warmer.
Booklist.
Kirkus Review.
School Library Journal.
5.0
K-3
Keywords: Tall tales; Size -- Fiction; Tall tales; Size -- Fiction; Tall tales